Project Based Learning Menggunakan Pendekatan Higher Order Thinking Skills (HOTS) untuk Meningkatkan Kemampuan Mahasiswa Abad 21 di Universitas Gunung Rinjani - Abdul Majid Junaidi; Rasyid Ridho Hamidy; Karomi Karomi (PALAPA, 2022)
In this era 4.0, students are required to have high-level thinking skills, which are better known as Higher Order Thinking Skills (HOTS). HOTS is the ability to think critically, logically, reflectively, metacognitively, and creatively to be able to solve the problems at hand. Globalization has brought its own changes and challenges in various fields including the field of Education. The learning program designed must be in line with 21st century education which requires graduates to be competent with a number of required skills. The purpose of this study was to find out how the implementation of Project-Based Learning (PjBL) through the Higher Order Thinking Skill approach was able to improve students' speaking skill at Gunung Rinjani University, and to find out how the HOTS-based PjBL process in public speaking courses. The participants in this study were 5th semester students in the Public Speaking subject of the English Education Study Program. This type of research is descriptive qualitative. Researchers used 3 data collection techniques, namely observation, interviews, and documentation. The results of this study showed positive responses by students regarding the implementation of PjBL through the HOTS approach, and were able to improve students' speaking skills and improve 21st century skills, namely critical thinking, creative, and able to solve problems, able to use technology media, and able to work together. In implementing PjBL using the HOTS approach, there are 4 steps that the lecturers implement, namely; preparation, implementation, development, and presentation.